P082 Informal opportunities for education about lifestyle factors in inflammatory arthritis. (23rd April 2022) - Robinson, Sandra; Bourke, Maurice; Scrafton, Nicola; Walker, David
Abstract: Background/Aims: Education of patients about their disease and treatments are a central part of the Nursing and AHP roles especially in chronic diseases such as arthritis. Different patients will require different approaches; layering and repetition of information are usually necessary. Recommended advice will also change over time with increased understanding and research, requiring updates for existing patients. In this situation any contact with the Rheumatology team is an opportunity to get health messages to patients. There is increasing data confirming the effect of obesity, exercise and smoking on response to treatment and outcomes in inflammatory arthritis. We were interested to explore if these messages had been delivered to established patients by our team. Methods: We designed a short, self-complete, questionnaire for patients asking about information they had received from the team on lifestyle advice. We included questions on drug education as a positive control as we were confident that all patients would have received education about this. 50 consecutive patients with either rheumatoid or psoriatic arthritis seen by one consultant were included. Results: The population was of 38 RA and 12 Psoriatic arthritis. Average duration of disease was 15yrs (Range 2-60). Average BMI was 28.4 (19.7-42.8). 29% were normal, 33% overweight and 38% obese. Only 59% said that they had moderate or a lot of education about their DMARDs and 11% reported having had none. However, 83% were moderately or very confident that they had sufficient information about the drug. No one reported no confidence. The most useful sources of information included the Doctors (50%) Nurses (37%) internet (24%) and booklets (9%). There was a strong correlation between amount of education and duration of disease (p < 0.001). Responses about how much information they had received from the team about lifestyle factors are shown in the table. There was a large range for all topics. Conclusion: It appears that patients do not always remember education about their drugs, but all have confidence that they know about the drugs. Messages about lifestyle factors are being given by the "Team", but around 50% of patients reported receiving little or no information on each topic. A more structured approach to these opportunities for education would be appropriate. Disclosure: S. Robinson: None. M. Bourke: None. N. Scrafton: None. D. Walker: Consultancies; Galapagos, Eli Lilly.